2019
DOI: 10.1177/0300060518814607
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of atrophic nonunion via autogenous ilium grafting assisted by vertical fixation of double plates: A case series of patients

Abstract: Objective To investigate the efficacy of the treatment of atrophic nonunion using structural autogenous ilium bone grafting in combination with vertical fixation of double plates. Methods This retrospective study analysed the clinical data from consecutive patients with atrophic nonunion who underwent autogenous ilium grafting in combination with double-plate vertical fixation. The injury type and the bone affected by nonunion, the duration of nonunion and the outcomes following surgery were recorded for all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Plating combined with bone grafting is the method most widely used to treat humeral shaft nonunion, as it achieves precise correction of the deformity and absolute stability, and enables the use of biologic augmentation [ 5 , 13 ]. One study reported a healing rate of 97% for anterior augmentation plating of aseptic humeral shaft nonunion [ 28 ], and a review of 36 studies found that plating with autologous bone grafting achieves a union rate of up to 98% in patients with humeral shaft nonunion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plating combined with bone grafting is the method most widely used to treat humeral shaft nonunion, as it achieves precise correction of the deformity and absolute stability, and enables the use of biologic augmentation [ 5 , 13 ]. One study reported a healing rate of 97% for anterior augmentation plating of aseptic humeral shaft nonunion [ 28 ], and a review of 36 studies found that plating with autologous bone grafting achieves a union rate of up to 98% in patients with humeral shaft nonunion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have reported the successful treatment of primary humeral diaphysis nonunion, few studies have specifically evaluated revision procedures for the salvage of persistent nonunion following failed initial nonunion interventions [ 2 , 8 ]. As our previous study showed that double plate fixation combined with structural autologous iliac bone grafting results in reasonable treatment outcomes for limb nonunion [ 13 ], the aim of the present study was to evaluate the clinical outcomes of this treatment strategy for recalcitrant humeral shaft nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies had proved that LCP combined with autologous iliac structural bone grafting can effectively treat aseptic limb nonunions [5,13], and many researchers advocated this treatment strategy. Gessmann et al [28] reported a 97% healing rate of anterior augmentation plating for aseptic humeral shaft nonunions after antegrade or retrograde intramedullary nailing.…”
Section: Discussionmentioning
confidence: 99%
“…Although many authors have reported on successful treatment of primary humeral diaphysis nonunion, few papers speci cally address the revision procedures for salvage of persistent nonunions following failed initial nonunion interventions [2,8]. As our team's previous study had shown that double plates combined with structural auto-iliac bone graft resulted in reasonable outcomes for treatment of patients with limb nonunion, we would like to know if persistent humeral shaft nonunions response well for this treatment strategy [13]. The purpose of this study was to report the authors' experience in the use of double plates combined with autogenous iliac bone graft in the treatment of recalcitrant humeral shaft nonunions.…”
Section: Introductionmentioning
confidence: 99%
“…During exposure, care was taken to identify and protect important structures, especially when the radial nerve was indicated, as the neurolysis would be necessary due to abundant scar tissue from multiple surgeries. The fracture nonunion site was opened and explored after original failed xation devices were removed (except in two patients who showed no gap between nonunion sites but remained a stable plating with at least layers of cortices xed at each side, where we left the previous plate in place and added a second plate), a thorough debridement was performed based on the Judet periosteal stripping technique [15], with the entire pseudocapsule, interposed brous tissue and sclerotic bone clearly excised until punctate bleeding was seen at the bony ends (Paprika sign) [5,16]. After opening the medullary canal using a drill bit, any angulation and rotation were corrected, and osteosynthesis was performed by using a 4.5-mm narrow LCP in compression mode to obtain cortex-to-cortex stability.…”
Section: Methodsmentioning
confidence: 99%